THE EFFECTS OF CONCENTRATE FEED AND MINERAL BLOCK ON THE DENSITY LEVEL AND MILK FAT CONTENT OF DAIRY CATTLE - Romziah Sidik; Desty Shafira; Mufasirin Mufasirin (Universitas Padjadjaran, 2017)
AbstractThe aim of this research is to understand the influence of concentrate feed and mineral block formulation on the densitylevel and milk fat of dairy cattle. The research was conducted on eight cross breed friesian holstein cows with ± 450 kg body weight and aged 2-4 years with milk production 8-11 liter/head/day. The experimental design of this study was complete randomized design with two treatments and each treatment was repeated four times. P0 (grass, tofu waste) and P1 (grass, tofu waste, concentrate feed, mineral block). The data was analyzed using t test (independent sample t test ). The software that was used to analyzed the data is Statistical Program for Social Science (SPSS) version 20 for Windows. The results showed that concentrate feed and mineral block did not significantly affect the density of milk and milk fat (p > 0.05). The mean density of milk in the P0 was 1.0255 and P1 was 1.0253. Mean while the average milk fat in the P0 was 3.27% and in P1 was 3.45%. Keywords : concentrate, mineral block, density, fat, dairy cow